Determinants of Micro Small and Medium Enterprise Revenue through Marketing Mix and Competitiveness in Electronic Commerce: Determinasi Pendapatan Usaha Mikro Kecil dan Menengah melalui Bauran Pemasaran dan Daya Saing di Perdagangan Elektronik - Siregar, Bakia Sarmita Utari; Nasution, Muhammad Irwan Padli; Nawawi, Zuhrinal M (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The rapid growth of the digital economy in Indonesia has provided new opportunities for micro, small, and medium enterprises to utilize online platforms such as Shopee to strengthen business performance. Specific background: Despite this potential, the digital adoption rate among enterprises in Medan City remains relatively low, indicating a gap in understanding how marketing strategies and competitiveness shape financial outcomes. Knowledge gap: Previous research has not sufficiently examined the mediating role of competitiveness between marketing mix components and enterprise revenue, particularly within a Sharia-compliant electronic commerce context. Aims: This study aims to analyze the contribution of product, price, place, and promotion to enterprise revenue through competitiveness as a mediating variable. Results: Using Structural Equation Modeling–Partial Least Squares on data from 102 enterprises operating on the Shopee platform, the findings show that product, price, and promotion have significant direct and indirect positive contributions to revenue through competitiveness, while place has only a direct contribution. Novelty: The research integrates marketing mix theory with Islamic business principles, positioning competitiveness as a strategic mediator for digital business growth. Implications: The results provide practical insights for enterprises and policymakers in developing ethical and data-driven marketing strategies to support sustainable competitiveness in Indonesia’s digital commerce ecosystem. Highlight Product, price, and promotion contribute significantly to enterprise revenue through competitiveness. Competitiveness acts as a mediating factor linking marketing mix and business performance. Islamic business principles strengthen ethical and sustainable digital commerce strategies. Keyword Marketing Mix, Competitiveness, Micro Small And Medium Enterprise, Electronic Commerce, Digital Business